We Heard It When We Were Young - Renteria, Chuy, 1985- (Book collections on Project MUSE., 2021)
"Most agree that West Liberty is a special place. The first majority Hispanic town in Iowa, it has been covered by media giants such as Reuters, Telemundo, NBC, and ESPN. But Chuy Renteria and his friends grew up in the space between these news stories, where a more complicated West Liberty awaits, full of small-town joy and horrific violence. We Heard it When We Were Young tells the story of a young boy, first generation Mexican-American, who is torn between cultures. Between immigrant parents trying to acclimate to Midwestern life and a town that was, by turns, supportive and disturbingly antagonistic. Chuy's story looks past the public celebrations of diversity to dive into the private tensions of a community reflecting the changing American landscape. There are culture clashes, breakdancing battles, fistfights, quinceañeras, vandalism, adventures on bicycles, and souped-up lowriders, all set to an early 2000s soundtrack. Chuy and his friends struggle to find their identities and reckon with intergenerational trauma and racism, in a town trying to do the same. Growing up in West Liberty was a never a simple journey, easily categorized as good or bad, safe or dangerous, but one filled with the depths of the human experience. A humorous and poignant reflection on coming of age, We Heard It When We Were Young puts its finger on a particular cultural moment at the turn of the millennium"--